Secondary prophylaxis of esophageal variceal treatment: Endoscopic sclerotherapy, band ligation and combined therapy - long-term results - Sedef ÖZDAL KURAN,; Dilek OĞUZ,; Erkan PARLAK,; Mehmet ASİL,; Bahattin ÇİÇEK,; Mesut KILIÇ,; Selçuk DİŞİBEYAZ,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-